Sun Yat-Sen and communism - Leng, Shao Chuan; Palmer, Norman D. (New York, 1960)
This book is an attempt to examine in depth the relations be tween Sun Yat-sen and Communism in the hope of casting new light on this complicated subject and of providing useful perspective on the history of modern China. The volume begins with a review of Sun's early contacts with the West and the process of his ideological development. Then it proceeds to analyze the reasons for Sun's Russian orientation and the effects of the Canton-Moscow alliance. To answer the question whether Communism is the logical climax of the work of Sun Yat-sen, the last part of the book not only examines the Communists' interpretations of his doctrine but compares the similarities and differences between Sun Yat-senism and Chinese Communism